Development of Multimedia Interactive Learning of Hydrosphere Material for High School - Alfi, Alfi Syahrinsi; L.R. Retno Susanti; Sardianto Markos Siahaan (JTP - Jurnal Teknologi Pendidikan, 2021)
The purpose of this research is the development of learning interactive multimedia at hydrosphere subject matter class X of high School. The development research which aims to produce learning interactive multimedia on subjects geography which is valid, practical and effective against the learning outcomes of students. Research development was using the Alessi and Trollip models. The steps of its developers, namely, planning, design, and development. On the stage of the alpha test do the validation on the validator I, validator II, and validator III. Test phase implemented in the class X IPS B SMA Muhammadiyah 6 Palembang. Data collection techniques using interviews, questionnaires, and tests. This research is valid and deserves to be tested after going through the process of validation of the validator I, validator II, and validator III. Through the beta test results the practicality shows the average value of 92,3 to the category of “very practical”. At the stage of field test learning outcomes of students showed an increase which amounted to 56,6 with the average results of the pretest of 24.6, while the posttest results amounted to 81,2 with N-gain of 0.75 then it belongs to the category of high, this shows that the learning interactive multimedia that is developed has a value of valid, practical, effectiveness and worth to use.